Kebijakan Kriminal Dalam Menghadapi Perkembangan Kejahatan Cyber Adultery - Gde Made Swardhana (Kertha Wicaksana, 2020)
One problem that is very troubling and gets the attention of various groups is the problem of cyber crime in the field of decency. The types of cyber crime in the field of decency that are being disclosed are cyber pornography (especially child pornography) and cyber sex, one of the studies of Cyber Adultery. The problems in this article are: (1). Can cyber adultery be encompassed with criminal provisions regarding adultery offenses? (2). What is the criminal policy in dealing with the development of cyber adultery crime in the future? In searching for this paper, normative legal research methods are used, namely discussing the issue of norms that are still vague in the sense that the provisions of the Criminal Code only indicate the existence of adultery in real terms. But what about the behavior carried out through cyber or cyberspace. Deception offense is offense related to (problem) decency. However, it is not easy to determine the limits or scope of moral offense because the definition and limits of morality are quite broad and can vary according to the views and values prevailing in society. Especially because the law itself is essentially minimal moral values, so basically every offense or criminal offense is a moral offense. In juridical manner, the offense of decency according to the Criminal Code currently in force consists of two groups of criminal acts, namely moral offenses. Provisions of positive criminal law related to criminal offenses in the field of decency including cyber adultery, among others are contained in: (a) Criminal Code; (b) Law No. 36 of 1999 concerning Telecommunications; (c) Press Law (Law No. 40/1999); (d) Broadcasting Law (No. 32/2002); and (e) Film Law (No. 8/1992). From these various laws, the provisions of criminal law can be related or related to moral issues. Although adultery, sex, porn is done in cyberspace (cyberspace).